The development of larvae of Brugia pahangi in several species ofinosquito in the laboratory - Suyoko, Suyoko (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1981)
Many species of mosquito were made to bite cat which contain microfilaria of Brugia pahangi in infective stage.Microfilaria will develop to infective stage (L3) in non-cibarial armature mosquitoes and will not in mosquitoes which have cibarial armature. This period depends on the species of mosquitoes. In Armigeres subalbatus we found first, second and third stage larvae on the fourth, sixth and seventh day.Key Words: Brugia pahangi cibarial armature mosquitoes - Armigeres - Mansonia -Â Anopheles